What Means Social Media in Authoritarian Regimes and For Authoritarian Regimes? - Muammer Fuat Aslan (Journal of Research in Social Sciences, 2022)
New technologies are important challengers for societies and states. There are many examples in hu-man history that technologies changed the way of thinking, the way of administration, and daily life. However, in the 21st century, new information and communication technologies are changing all these institutions very quickly. Moreover, it is difficult to follow all the updates. The digital divide is a real big challenge in people’s lives and futures. Therefore, the importance of the digital divide becomes more visible through modernization and digitization. Although people want to follow the developments in the digital area, it is not easy when there is a digital gap. Hence, liberation technologies help people to stay up to date. It also expands a person's rights and freedoms, so it can be seen as a threat by autocratic regimes. During the Egyptian Uprisings, social media be-came the main tool of citizens using liberation technologies. There was a mass protest from near and far, hence, a resource model of political participation was used to understand the high level of participation in uprisings. The resources were time, money, and civil skills. When the Egyptian uprising has resulted in the resignation of the president, Hosni Mubarak, social media played a key role in achieving important successes for citizens of Egypt. Consequently, the impact of social media in authoritarian regimes was discussed.